Znaczenie psalmów w życiu chrześcijanina w świetle nauczania Benedykta XVI - Pagacz, Małgorzata (Poznańskie Studia Teologiczne, 2022)
This article presents the importance of the Psalms in the life of a Christian in the light of the teaching of Benedict XVI. The Psalms allow us to dialogue with God in His words. They are a true school of prayer: they teach us to turn to God in every state of mind, in every situation and with every emotion that man experiences. The Psalms take on their full meaning and value in the light of the Person of Jesus Christ. In praying the psalms, the Christian addresses himself to the Father in Christ and with Christ, opening himself to a new perspective which has its ultimate interpretative key in the paschal mystery. In this way he comes to know the Saviour better and can deepen his relationship with Him. Praying the Psalms is important in the contemporary context because, in times of crisis of hope and forgetfulness of God, it teaches us to seek reliable support in the Creator and Saviour and to turn always to Him.